1999
DOI: 10.1002/(sici)1097-0290(19990905)64:5<509::aid-bit1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cellular properties from external fields and resulting induced velocity: Cellular hydrodynamic diameter

Abstract: An experimental technique is discussed in which the size distribution of a population of cells is determined by calculating each cell's settling velocity. The settling velocity is determined from microscopically obtained images which were recorded on SVHS tape. These images are then computer imaged and processed, and the cell's location and velocity are determined using a computer algorithm referred to as cell tracking velocimetry (CTV). Experimental data is presented comparing the distribution of human lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…As has been reported in a previous publication (Chalmers et al, 1999b;Jin et al, 2008), the settling velocity of the cells and the polystyrene microspheres can be related to the density difference between the cells (or microspheres) and the cell diameter by:…”
Section: Intrinsic Magnetophoretic Mobilitymentioning
confidence: 71%
See 2 more Smart Citations
“…As has been reported in a previous publication (Chalmers et al, 1999b;Jin et al, 2008), the settling velocity of the cells and the polystyrene microspheres can be related to the density difference between the cells (or microspheres) and the cell diameter by:…”
Section: Intrinsic Magnetophoretic Mobilitymentioning
confidence: 71%
“…We are not aware of any reported density values for Detriot 562 or Cal 27; however, we previous reported that the density difference for one cancer cell line, MCF-7, is 30 kg/m 3 (Chalmers et al 1999b). …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The differences are likely related to the cell density estimation, nonuniform density distribution in the cell population, and the departure from spherical cell shape (assumed in Eq. 6) (42). MSC mean diameter was 12.7 ± 2.1 μm, cardiac fibroblast mean diameter was 11.5 ± 1.6 μm, and KG‐1a cell mean diameter was 10.4 ±1.7 μm.…”
Section: Methodsmentioning
confidence: 99%
“…This method is useful for trapping cells having surface markers but it cannot discriminate between cells having varying densities of surface markers. To confer marker density discrimination, continuous magnetophoretic (MAP) sorting of immunomagnetically labeled cells in a laminar flow profile has been demonstrated [82], [83]. In this scheme, cells are deflected by a quadrapole magnetic field in proportion to the degree of labeling and emerge from the sorting chamber along a trajectory that allows their differential recovery.…”
Section: ) Dielectrophoretic-magnetophoretic-fff (Map-dep-fff)mentioning
confidence: 99%